Streptococcus mutans and Actinomyces naeslundii Interaction in Dual-Species Biofilm - de Oliveira, Rosa Virginia Dutra (Microorganisms, 2020)
The study of bacterial interaction between Streptococcus mutans and Actinomyces naeslundii may disclose important features of biofilm interspecies relationships. The aim of this study was to characterize—with an emphasis on biofilm formation and composition and metabolic activity—single- and dual-species biofilms of S. mutans or A. naeslundii, and to use a drip flow reactor (DFR) to evaluate biofilm stress responses to 0.2% chlorhexidine diacetate (CHX). Single- and dual-species biofilms were grown for 24 h. The following factors were evaluated: cell viability, biomass and total proteins in the extracellular matrix, 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide—“XTT”—reduction and lactic acid production. To evaluate stress response, biofilms were grown in DFR. Biofilms were treated with CHX or 0.9% sodium chloride (NaCl; control). Biofilms were plated for viability assessment. Confocal laser-scanning microscopy (CLSM) was also performed. Data analysis was carried out at 5% significance level. S. mutans viability and lactic acid production in dual-species biofilms were significantly reduced. S. mutans showed a higher resistance to CHX in dual-species biofilms. Total protein content, biomass and XTT reduction showed no significant differences between single- and dual-species biofilms. CLSM images showed the formation of large clusters in dual-species biofilms. In conclusion, dual-species biofilms reduced S. mutans viability and lactic acid production and increased S. mutans’ resistance to chlorhexidine.